Big Book Terhadap Kemampuan Mengenal Ekspresi Emosi - Nidika, Dwi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
This study aims to determine the effect on the ability to know the Big Book of emotional expression in children aged 2-3 years in PAUD Terpadu Fi Ahsani Taqwim Temanggung. Subjects in this study were selected using purposive sampling method, Research carried out by the design of experiment one group pretest posttest. The experimental group consisted of 30 research subjects, who received stimulation treatment using the Big Book. Methods of data collection is done through observation of the subject's ability to recognize emotional expressions angry, happy, sad, surprised. Conclusions in this research that analyzed data using a non-parametric test by using Wilcoxon Signed Rank Test with SPSS For Windows Version 16.0. Conclusion of the study is the positive influence on the ability to know the Big Book of emotional expression in PAUD Terpadu Fi Ahsani Taqwim Temanggung. The new findings show that the Big Book can improve the ability to know the expression of emotions.